Comparative Analysis of TopIndoku Resellers: Unveiling B2B Dynamics Between Kalimantan Barat and Beyond - Seiko Manito; Nur Afifah; Erna Listiana; Barkah Barkah; Wenny Pebrianti (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This research discusses the influence of service quality, customer satisfaction on loyalty of Topindoku resellers in West Kalimantan and outside West Kalimantan. This research also compared the responses of Topindoku resellers in West Kalimantan and outside West Kalimantan. This research uses quantitative methods with a survey approach. Data will be collected through the use of a questionnaire which will be distributed to Topindoku resellers in West Kalimantan and outside West Kalimantan. Data analysis will involve statistical techniques such as difference tests and path analysis to test the relationship between the variables studied. The results of the research show that there are differences in Service Quality responses between Topindoku resellers in West Kalimantan and outside West Kalimantan. However, there was no difference in Customer Satisfaction and Loyalty responses to Topindoku resellers in West Kalimantan and outside West Kalimantan. The results of service quality have a positive and significant effect on loyalty towards Topindoku resellers in West Kalimantan and outside West Kalimantan. Service quality has a positive and significant effect on customer satisfaction with Topindoku resellers in West Kalimantan and outside West Kalimantan. Customer satisfaction has a positive and significant effect on loyalty towards Topindoku resellers in West Kalimantan and outside West Kalimantan. Apart from that, customer satisfaction can act as a mediator between service quality and loyalty towards Topindoku resellers in West Kalimantan and outside West Kalimantan.